The Role of Bone Marrow-Derived Cells during Ectopic Bone Formation of Mouse Femoral Muscle in GFP Mouse Bone Marrow Transplantation Model - Takabatake, Kiyofumi (Int J Med Sci, 2018)
Multipotential ability of bone marrow-derived cells has been clarified, and their involvement in repair and maintenance of various tissues has been reported. However, the role of bone marrow-derived cells in osteogenesis remains unknown. In the present study, bone marrow-derived cells during ectopic bone formation of mouse femoral muscle were traced using a GFP bone marrow transplantation model. Bone marrow cells from C57BL/6-Tg (CAG-EGFP) mice were transplanted into C57BL/6 J wild type mice. After transplantation, insoluble bone matrix (IBM) was implanted into mouse muscle. Ectopic bone formation was histologically assessed at postoperative days 7, 14, and 28. Immunohistochemistry for GFP single staining and GFP-osteocalcin double staining was then performed. Bone marrow transplantation successfully replaced hematopoietic cells with GFP-positive donor cells. Immunohistochemical analyses revealed that osteoblasts and osteocytes involved in ectopic bone formation were GFP-negative, whereas osteoclasts and hematopoietic cells involved in bone formation were GFP-positive. These results indicate that bone marrow-derived cells might not differentiate into osteoblasts. Thus, the main role of bone marrow-derived cells in ectopic osteogenesis may not be to induce bone regeneration by differentiation into osteoblasts, but rather to contribute to microenvironment formation for bone formation by differentiating tissue stem cells into osteoblasts.